SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS BERBASIS MULTIUSER DI SMK PATI UNUS KARANGAWEN DEMAK - Kasih Purwantini; Danang Danang; Siti Nasekah (Universitas Sains dan Teknologi Komputer, 2020)
This study designed a system that is able to assist companies in calculating cash receipts and disbursements. The Accounting Information System for Cash Receipts and Expenditures will be equipped with the use of user log-ins to maintain the level of data security so that not just anyone can misuse the data. The system designed will also be equipped with security of access rights and data storage systems, providing a database using the Visual Basic 6.0 programming language that holds records of cash receipts and disbursements to be a good report, summarizing the process of moving data from ledgers to becoming cash reports flow, and can document each period's report so that it can be grouped properly. The research method used is the Borg and Gall R&D research approach which consists of 10 stages, out of 10 R&D stages the author only conducts the research approach to the 6th stage alone. and monitoring cash flow very well. In addition, it can also produce reports that are precise, accurate and efficient.